Busted ghosts: Rediscovery of supposedly destroyed types of Brazilian Mimosa (Leguminosae, Mimosoideae) - Borges, Leonardo Maurici; Pirani, José Rubens (Phytotaxa, 2014)
In his monograph for neotropical Mimosa, Rupert Barneby made seemingly effective lectotypifications for a few binomials originally published by Taubert. He chose specimens in the Berlin herbarium (B), which he supposed had been destroyed. We hereby bring new evidence for the absence of these specimens in Berlin, their being in Hamburg (HBG) instead, and we designate them as lectotypes for the names in question.